Accuracy of velocities from repeated GPS measurements - Akarsu, V.; Sanli, D. U.; Arslan, E. (COPERNICUS GESELLSCHAFT MBH, 2015)
Today repeated GPS measurements are still in use, because we cannot always employ GPS permanent stations due to a variety of limitations. One area of study that uses velocities/deformation rates from repeated GPS measurements is the monitoring of crustal motion. This paper discusses the quality of the velocities derived using repeated GPS measurements for the aim of monitoring crustal motion. From a global network of International GNSS Service (IGS) stations, we processed GPS measurements repeated monthly and annually spanning nearly 15 years and estimated GPS velocities for GPS baseline components latitude, longitude and ellipsoidal height. We used web-based GIPSY for the processing. Assuming true deformation rates can only be determined from the solutions of 24 h observation sessions, we evaluated the accuracy of the deformation rates from 8 and 12 h sessions. We used statistical hypothesis testing to assess the velocities derived from short observation sessions. In addition, as an alternative control method we checked the accuracy of GPS solutions from short observation sessions against those of 24 h sessions referring to statistical criteria that measure the accuracy of regression models. Results indicate that the velocities of the vertical component are completely affected when repeated GPS measurements are used. The results also reveal that only about 30% of the 8 h solutions and about 40% of 12 h solutions for the horizontal coordinates are acceptable for velocity estimation. The situation is much worse for the vertical component in which none of the solutions from campaign measurements are acceptable for obtaining reliable deformation rates.
Keywords: NOISE; OPUS; Geology; Meteorology & Atmospheric Sciences; Water Resources